Popular Music Education: A Call to Action. (September 2019) - Powell, Bryan; Smith, Gareth Dylan; West, Chad; Kratus, John
This is the editors' introduction to the Special Focus Issue on Popular Music Education. Also included is a forward from Robert A. Cutietta, editor of the 1991 Music Educators Journal Special Focus Issue on Popular Music Education.